Pengaruh Yoga Prenatal Terhadap Kualitas Tidur Ibu Hamil Trimester III: Pengaruh Yoga Prenatal Terhadap Kualitas Tidur Ibu Hamil Trimester III (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Prenatal yoga is a kind of exercise specifically designed for pregnant women. Pregnant women who practice prenatal yoga may reap a variety of physical and psychological advantages by training their body and breath. Prenatal yoga will educate pregnant women to adapt to new conditions, concentrate on breathing and body awareness, and decrease anxiety. It will also assist pregnant women relax and develop the muscles that will be utilized for birthing later. In a span of 12 days, the research was repeated three times. Pre-experimental, one group, pre-test, post-test design comprised the study methodology. The population for this research consisted of 35 pregnant women who were all aged 28 to 36 weeks and had been homogenized in the working area of the Banyuputih Public Health Center in Situbondo Regency. 32 pregnant women were included in the sample using a proportionate random sampling approach. Questionnaire and SOP were the instruments employed. editing, scoring, coding, and tabulating are all forms of data processing. Wilcoxon statistical analysis. According to the study's findings, 29 pregnant women and 31 other respondents (96.9%) had poor sleep quality before practicing yoga, while 29 other respondents (96.9%) had excellent sleep quality after. 29 expectant mothers in all (90.6%). based on a Wilcoxon test statistical analysis with a significance threshold of p=0.000. Keywords: Yoga Exercise, Sleep Quality of Pregnant Women